Trends in biotechnological production of fuel ethanol from different feedstocks - Sánchez, Óscar J.; Cardona, Carlos A. (Bioresource technology, 2008)
Present work deals with the biotechnological production of fuel ethanol from different raw materials. The different technologies for producing fuel ethanol from sucrose-containing feedstocks (mainly sugar cane), starchy materials and lignocellulosic biomass are described along with the major research trends for improving them. The complexity of the biomass processing is recognized through the analysis of the different stages involved in the conversion of lignocellulosic complex into fermentable sugars. The features of fermentation processes for the three groups of studied feedstocks are discussed. Comparative indexes for the three major types of feedstocks for fuel ethanol production are presented. Finally, some concluding considerations on current research and future tendencies in the production of fuel ethanol regarding the pretreatment and biological conversion of the feedstocks are presented.